PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA DENGAN MENGGUNAKAN METODE DISCOVERY - Dewi, Susi Gustina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
The research is motivated by the inability of the students have the right to instill the concept of learning. Besides that teacher rarely create meaningful learning methods. There fore, the authors apply the discovery method in this study with the aim of describing the lesson plan, the implementation of learning, and student learning outcomes. The research used qualitative and quantitative research approaches. The result of research can be seen from the result of observations of the lesson plan that is 74,95% in the first cycle and second cycle is 85,7%. Moreover obtained subsequent to the implementation of teacher activity is 73,1% in the first cycle and second  cycle is 89,2%. The result of observations activities of student is 69,7 % in the first cycle and second cycle is 85,7%. Whereas the learning outcomes of students in the first cycle to obtain an average of 65,7 and the second cycle of 77,95 this suggest that the discovery method can improve science learning outcomes. Kata Kunci : hasil belajar, IPA, pembelajaran, dan metode discovery